Reactor Grids for Prioritizing Syphilis Investigations: Are Primary Syphilis Cases Being Missed?. Issue 10 (October 2018) - Cha, Susan; Matthias, James M.; Rahman, Mohammad; Schillinger, Julia A.; Furness, Bruce W.; Pugsley, River A.; Kidd, Sarah; Bernstein, Kyle T.; Peterman, Thomas A.
Abstract : Background: Health departments prioritize investigations of reported reactive serologic tests based on age, gender, and titer using reactor grids. We wondered how reactor grids are used in different programs, and if administratively closing investigations of low-titer tests could lead to missed primary syphilis cases. Methods: We obtained a convenience sample of reactor grids from 13 health departments. Interviews with staff from several jurisdictions described the role of grids in surveillance and intervention. From 5 jurisdictions, trends in reactive nontreponemal tests and syphilis cases over time (2006–2015) were assessed by gender, age, and titer. In addition, nationally-reported primary syphilis cases (2013–2015) were analyzed to determine what proportion had low titers (⩽1:4) that might be administratively closed by grids without further investigation. Results: Grids and follow-up approaches varied widely. Health departments in the study received a total of 48, 573 to 496, 503 reactive serologies over a 10-year period (3044–57, 242 per year). In 2006 to 2015, the number of reactive serologies increased 37% to 169%. Increases were largely driven by tests for men although the ratios of tests per reported case remained stable over time. Almost one quarter of reported primary syphilis had low titers that would be excluded by most grids. The number of potentially missed primary syphilis cases varied by gender and age with 41- to 54-year-old men accounting for most. Conclusions: Reactor grids that close tests with low titers or from older individuals may miss some primary syphilis cases. Automatic, computerized record searches of all reactive serologic tests could help improve prioritization. Abstract : Reactor grids may miss low-titer primary syphilis cases. Supplemental digital content is available in the text.